2020
DOI: 10.1161/hypertensionaha.119.14230
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Pressure With Outcomes in Acute Stroke Thrombectomy

Abstract: Limited data exist evaluating the effect of blood pressure (BP) on clinical outcomes among patients with acute ischemic stroke with large vessel occlusion treated with mechanical thrombectomy (MT). We sought to evaluate the association of BP levels on clinical outcomes among patients with acute ischemic stroke with large vessel occlusion treated with MT. Studies were identified that reported the association of systolic BP (SBP) or diastolic BP levels before, during, or after MT on the outcomes of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 64 publications
1
77
0
2
Order By: Relevance
“…The current guidelines from the American Heart Association/American Stroke Association guidelines arbitrarily recommend blood pressure (BP) control of <180/105 mm Hg during and after MT. However, data regarding guidance for optimal BP management among patients treated with MT remain scarce ( 4 ). Theoretically, the target of BP control should be lower in patients following MT because of the high hemorrhagic transformation risk after clot removal ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current guidelines from the American Heart Association/American Stroke Association guidelines arbitrarily recommend blood pressure (BP) control of <180/105 mm Hg during and after MT. However, data regarding guidance for optimal BP management among patients treated with MT remain scarce ( 4 ). Theoretically, the target of BP control should be lower in patients following MT because of the high hemorrhagic transformation risk after clot removal ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the significant heterogeneity among the different hemodynamic parameters used, no meta-analysis of association was performed. Although a recent meta-analysis concerning BP management before, during and after AIS was recently published (26), this very analysis appropriately excluded overlapping data [i.e., studies involving the same population, which was the case in the present analysis for three studies from the same author (6,13,30)] and did not focus on successfully reperfused patients only. The present analysis therefore provides updated additional data and seems to point toward similar results, regarding the impact of BP values post-EVT and the need of quality RCT regarding this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observational studies have recently outlined the association between higher post-reperfusion BP values and sICH or worse functional outcomes, notably according to the reperfusion status (6-9, 11, 13-25). A recent systematic review and meta-analysis focusing on mean systolic BP (SBP) and diastolic BP (DBP) suggested that increased BP after EVT was associated with sICH and 3-month functional dependence (26). Still, many questions remain unanswered such as the specific BP target to achieve, the best pharmacological approach according to the reperfusion status and the impact of BP variability after EVT.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efficacy of EVT, many patients with LVO stroke still suffer morbidity, mortality, and functional dependence in longitudinal studies ( 7 , 18 ). Observational studies, including a recent meta-analysis, have shown higher rates of HT, worse outcomes, and increased mortality in patients with higher peak SBP values or hemodynamic variability in the first 24 hours after EVT ( 15 , 19 21 ). However, it remains unclear if post-procedural hypertension is simply an epiphenomenon, or if it reflects a valid therapeutic target.…”
Section: Blood Pressure Management Following Thrombectomymentioning
confidence: 99%